(3QSGdI GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI GdfaS ddTjN GdQFjS NjQ GdeSGhi HeGOjf HGdMeO dhGgH GdYbd Ydi MeOg hHYO adhdG Cf GdYGOI ShYJ ddg s
(3BNQgG (B:s
(3hHOhdJg OhdJgG hjQLY HCjGeg CjGegG hjQJaY HecGfgG ecGf CgdgG s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MceI hadSaI(B) s
Keywords: (3eJaQbGJs